Chapter Competizione e complessità nel sistema internazionale tra equilibri e caos - Ragionieri, Rodolfo (Studi e saggi, 2022)
The study of complexity in world politics began painstakingly in the 1980s on the initiative of authors such as James Rosenau, and looks at different types of complexity such as non-linear interactions, the interaction between actors at different levels (turbulence), the emergence of structures. The chapter intends to analyze the contribution the study of competition processes can provide by means of the theory of dynamical systems. For this purpose, nonlinear equations derived from Richardson's and equations formulated in the framework of population theories concerning crime or terrorism are considered. Finally, the need to move on to the theory of self-organization and emergent structures is indicated.